La representación icónico-alegórica de lo sobrenatural en siete cuentos de aparecidos del Ecuador (Crítica) - Robalino Caicedo, Vicente Eduardo (2021)
In this essay an analysis and interpretation of seven tales of apparitions from Ecuador is made, for which the author starts from the following question: How is the iconic-allegorical representation of the supernatural constructed in the selected stories? To answer this question, the kinesic and proxemic spaces of the selected stories are analyzed. Of these two semiotic categories, the iconic image stands out as a model of the spaces of the supernatural, together with the geographical spaces where the action of these stories takes place. From this relationship —natural space–geographical space— emerge the fantastic effects. However, in some of these stories, the dominant presence of the moralizing-allegory destroys the perception of the fantastic as in Vico y el duende, El enano (duende), and to a great extent also in Mariangula. On the other hand, other stories, such as, for example, Almita en pena, enrich the iconic image of the supernatural with the incorporation of the rite and the symbol.